Feeding-Regime-Dependent Intestinal Response of Rainbow Trout after Administration of a Novel Probiotic Feed - Marek Ratvaj; Ivana Cingeľová Maruščáková; Peter Popelka; Adriána Fečkaninová; Jana Koščová; Natália Chomová; Jan Mareš; Ondřej Malý; Rudolf Žitňan; Martin Faldyna; Dagmar Mudroňová (Animals, 2023)
Intensive fish farming is associated with a high level of stress, causing immunosuppression. Immunomodulators of natural origin, such as probiotics or phytoadditives, represent a promising alternative for increasing the immune function of fish. In this study, we tested the autochthonous trout probiotic strain L. plantarum R2 in a newly developed, low-cost application form ensuring the rapid revitalization of bacteria. We tested continuous and cyclic feeding regimes with regard to their effect on the intestinal immune response and microbiota of rainbow trout. We found that during the continuous application of probiotic feed, the immune system adapts to the immunomodulator and there is no substantial stimulation of the intestinal immune response. During the cyclic treatment, after a 3-week break in probiotic feeding and the reintroduction of probiotics, there was a significant stimulation of the gene expression of molecules associated with both cellular and humoral immunity (CD8, TGF-β, IL8, TLR9), without affecting the gene expression for IL1 and TNF-α. We can conclude that, in aquaculture, this probiotic feed can be used with a continuous application, which does not cause excessive immunostimulation, or with a cyclic application, which provides the opportunity to stimulate the immunity of trout, for example, in periods of stress.